2013
DOI: 10.1186/1742-2094-10-68
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β peptide-induced extracellular S100A9 depletion is associated with decrease of antimicrobial peptide activity in human THP-1 monocytes

Abstract: BackgroundS100A9 protein (myeloid-related protein MRP14, also referred to as calgranulin B) is a reliable marker of inflammation, an important proinflammatory factor of innate immunity and acts as an additional antimicrobial peptide in the innate immune system. Evidence indicates that S100A9 contributes to Alzheimer’s disease (AD) pathology, although the precise mechanisms are not clear.MethodsWe were interested to study the mechanisms of S100A9 release upon Aβ1-42 stimulation, the potential roles of extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…S100A9 regulates γ-secretase and BACE1 expression and activity ( Kummer et al, 2012 ; Li et al, 2014 ), and S100B and S100A1 regulate APP levels ( Zimmer et al, 2005 ; Anderson et al, 2009 ; Mori et al, 2010 ). S100A7, S100A8, S100A9, and S100B have been found to influence Aβ levels ( Qin et al, 2009 ; Lee et al, 2013 ; Lodeiro et al, 2017 ; Cristovao et al, 2018 ). Moreover, S100B and S100A6 have been found to reduce zinc levels and senile plaque load in preclinical models ( Roltsch et al, 2010 ; Hagmeyer et al, 2017 ; Tian et al, 2019 ).…”
Section: Classification Of Ad Biomarkersmentioning
confidence: 98%
“…S100A9 regulates γ-secretase and BACE1 expression and activity ( Kummer et al, 2012 ; Li et al, 2014 ), and S100B and S100A1 regulate APP levels ( Zimmer et al, 2005 ; Anderson et al, 2009 ; Mori et al, 2010 ). S100A7, S100A8, S100A9, and S100B have been found to influence Aβ levels ( Qin et al, 2009 ; Lee et al, 2013 ; Lodeiro et al, 2017 ; Cristovao et al, 2018 ). Moreover, S100B and S100A6 have been found to reduce zinc levels and senile plaque load in preclinical models ( Roltsch et al, 2010 ; Hagmeyer et al, 2017 ; Tian et al, 2019 ).…”
Section: Classification Of Ad Biomarkersmentioning
confidence: 98%
“…Antimicrobial activity of S100A9 also have been reported. The mechanism behind antimicrobial activity is the monomeric form of amyloid beta (Aβ) 1-42 that is negatively regulated by the innate immune system by downregulating the secretion of S100A9 [33]. However, our data showed that only GCF S100A9 level was signi cantly lower in periodontitis patients than in healthy adults.…”
Section: Discussionmentioning
confidence: 67%
“…Among the 5 classifier proteins, S100A9 is the only one associated with AD [67][68][69][70][71][72]. S100A9 in the brain was reported to associate with the neuropathological hallmarks of AD and contribute to AD pathology [67][68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…S100A9 in the brain was reported to associate with the neuropathological hallmarks of AD and contribute to AD pathology [67][68][69][70][71][72]. For example, induction of S100A9 was observed in the brain of AD animal model Tg2576 and in human AD brain.…”
Section: Discussionmentioning
confidence: 99%